2014
DOI: 10.1111/1574-6968.12380
|View full text |Cite
|
Sign up to set email alerts
|

Toxin-antitoxinvapBClocus participates in formation of the dormant state inMycobacterium smegmatis

Abstract: Toxin-antitoxin (TA) loci are widely spread in bacterial plasmids and chromosomes. Toxins affect important functions of bacterial cells such as translation, replication and cell-wall synthesis, whereas antitoxins are toxin inhibitors. Participation in formation of the dormant state in bacteria is suggested to be a possible function of toxins. Here we show that overexpression of VapC toxin in Mycobacterium smegmatis results in development of morphologically distinct ovoid cells. The ovoid cells were nonreplicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…1A). It has recently been demonstrated that Rv2866 (relG) causes mycobacterial cells to become filamentous (Miallau et al, 2013), while the V apC M.smegmatis toxin potentiates the development of ovoid cells (Demidenok et al, 2014). The polar expansion of mycobacterial cells following relE Mtb expression, and the elongation following relG expression, suggest that Rel Mtb toxins impact lipid biosynthesis, cell envelope assembly, and/or cell division.…”
Section: Discussionmentioning
confidence: 99%
“…1A). It has recently been demonstrated that Rv2866 (relG) causes mycobacterial cells to become filamentous (Miallau et al, 2013), while the V apC M.smegmatis toxin potentiates the development of ovoid cells (Demidenok et al, 2014). The polar expansion of mycobacterial cells following relE Mtb expression, and the elongation following relG expression, suggest that Rel Mtb toxins impact lipid biosynthesis, cell envelope assembly, and/or cell division.…”
Section: Discussionmentioning
confidence: 99%
“…M. tuberculosis is the causative agent of tuberculosis and contains an unusually high number of VapBC systems ( 30 ). The VapBC system, which is implicated in dormant state formation ( 31 ), virulence ( 58 ), and stress response ( 59 ), is an interesting target for the rational design of an antimicrobial peptide against tuberculosis ( 26 ). Via biochemical analysis, we confirmed that M. tuberculosis VapC30 is an Mg 2+ and Mn 2+ dependent ribonuclease that inhibits cellular growth.…”
Section: Discussionmentioning
confidence: 99%
“…In M. tuberculosis , more than half of the TA systems belong to the VapBC family (47 of 88 putative TA systems) ( 30 ), and vapBC loci are tightly associated with virulence factors and pathogenicity factors ( 18 ). The VapBC family may therefore contribute to the extreme persistence and pathogenic success of M. tuberculosis ( 31 ). Although efforts to develop antimicrobial drugs based on TA systems are emerging, antimicrobial peptides based on a structural rationale remain limited to the toxin structure of Bacillus anthracis MoxT ( 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a more concrete example, E. coli mutants of the HipB antitoxin but with functional HipA toxin were nonculturable altogether (100). Demidenok and colleagues showed that overexpression of the VapB antitoxin prevented cells from entering the VBNC state, while overexpression of the VapC toxin induced the VBNC state (108). Similarly, overexpression of the MParE2 toxin led to a decline in culturability due to entry into the VBNC state (109).…”
Section: Overlapping Molecular Mechanismsmentioning
confidence: 99%